2008
DOI: 10.1093/sleep/31.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy and Safety of Zolpidem Extended-Release 12.5 mg, Administered 3 to 7 Nights Per Week for 24 Weeks, in Patients With Chronic Primary Insomnia: A 6-Month, Randomized, Double-Blind, Placebo-Controlled, Parallel-Group, Multicenter Study

Abstract: These findings establish the efficacy of 3 to 7 nights per week dosing of zolpidem extended-release 12.5 mg for up to 6 months. Treatment provided sustained and significant improvements in sleep onset and maintenance and also improved next-day concentration and morning sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(101 citation statements)
references
References 24 publications
2
94
0
5
Order By: Relevance
“…Erman Fourteen additional studies met inclusion criteria but could not be included in meta-analysis due to inadequate data sets. 71,[83][84][85][86][87][88][89][90][91][92][93][94][95] Pertinent results from these studies are noted independently of meta-analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…Erman Fourteen additional studies met inclusion criteria but could not be included in meta-analysis due to inadequate data sets. 71,[83][84][85][86][87][88][89][90][91][92][93][94][95] Pertinent results from these studies are noted independently of meta-analysis results.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the eszopiclone can exhibit different binding properties on GABA A receptor, compared to zolpidem it is also less selective for the GABA A receptor α 1 -subunit. 11 Also in a double-blind, randomized, placebo-controlled trial it improved daytime functioning at a dose of 3 mg without evidence of tolerance, dependence, or abuse.…”
Section: Eszopiclonementioning
confidence: 97%
“…Four trials studied the general adult population with pain [80][81][82][83][84] and three assessed the efficacy of CBT-I in older adults with pain. 79,85,86 McCurry is a second publication of an earlier trial analyzing only a portion of the participants with pain.…”
Section: Overview Of Studiesmentioning
confidence: 99%